An investigation of the epidemiology of age-related maculopathy in the UK - Wilde, Craig (2018)
Although there are several publications on the prevalence of AMD in the UK, there remains a paucity of data from population studies from this country. This study provides the most detailed exploration of the epidemiology of AMD within a UK community based population to date. It provides contemporary prevalence rates for different stages of AMD in a UK population, and indicates the prevalence of advanced AMD is more common than previously thought (4.3%), reaching a maximum of 21.2% for the over 90 year age group. Despite this high prevalence of advanced AMD, approximately 50% of the over 65-year old population have no or minimal signs of ARM. This study confirms that persons with the earlier and intermediate stages of AMD are asymptomatic. The prevalence of GA is more common than that of nAMD, with GA being 1.7 and 1.6 times more prevalent in the right and left eyes respectively. This difference remains when analysed for the worse eye, with GA still being 1.3 times more common than nAMD. For the first time in a large population based study, this thesis reports self- satisfaction with participant’s vision and association with AMD severity/grade. It shows that a large proportion of individuals (61.0%) with GA in their worse eye still remain satisfied with their vision. When AMD grade in the worse eye was the variable, nAMD is the only stage at which the majority of participants are dissatisfied (59.4%) with the level of their vision. When the better eye was evaluated, there was a significant increase in subject dissatisfaction with vision, particularly for individuals with bilateral nAMD, with almost 90% of subjects being dissatisfied with the quality of their vision. We describe in detail the features of GA within this UK population. The information will be useful in the design of future clinical trials that evaluate the development or progression of GA or its treatment, as well as modelling the impact of GA on sight loss in the UK. In summary, GA has a prevalence of 2.5% for the worse eye in the over 65 year Bridlington population, increasing with age to a maximum of 9.84% for those aged 85 to 90 years. Bilateral GA is not an infrequent finding, occurring in 34% of subjects with known GA. In the mainstay it is largely an eccentric condition, with only 31.5% of involved eyes having subfoveal GA. The majority of GA appears to occur in the perifoveal region, particularly GA that is associated with conventional drusen. Only a minority eyes with GA in the community have large areas of atrophy over 17.5mm2; the mean area of GA was 4.51mm2. This thesis, in chapter 4, demonstrates there is a clear association between GA phenotype and the phenotype of drusen identified within the remaining fundus. In chapter 4 it is demonstrated that RPD are, in the mainstay, associated with horseshoe shaped GA, and have a high prevalence of 55.9% within this group. This is a previously unreported finding. The prevalence of RPD in eyes with round GA is considerably less (8.3%). There is a suggestion that GA in eyes with RPD may have larger areas of atrophy and are less likely to have foveal involvement. However, the mean VA remains the same secondary to a diffuse, central retinal pigment epitheliopathy that appears to be associated with RPD horseshoe shaped GA. This again, is a previously unreported finding. Unlike in the previous hospital based literature, we demonstrate most multifocal GA is still associated with conventional drusen. In chapter 5, the prevalence of RPD in the over 65 year Bridlington population is estimated as 5.06% for either eye. This is the highest population based prevalence of RPD reported to date, and represents the only detailed report of the epidemiology of RPD within a UK population. Out of all the population based prevalence studies performed to date, the BEAP Study is the only one to utilise and analyse the red-free channel of the FP, which enhanced RPD detection within the study by 13%. As such, this study possibly represents the most accurate measure of RPD prevalence to date. In the present study, the prevalence of RPD increases significantly with age, reaching a maximum of 27% in the over 90-year age group. The BEAP study confirms that RPD occur most frequently in the upper outer subfield. Unlike previously reported, however, RPD do occur within the central subfield, albeit in a form that differs slightly in its appearance, and significantly reduced size. The BEAP study confirms that RPD have a female preponderance, with a higher gender specific prevalence rate in women. They are commonly found in association with other signs of ARM, including drusen over 125µm (50 % of the time) and pigmentary changes. Isolated RPD, in the absence of conventional drusen, is an uncommon finding but does occur. Approximately 1 in 4 subjects with advanced AMD will have evidence of RPD in either eye. This thesis also reports, for the first time, the prevalence of RPD in eyes with PPCNVs. There is a suggestion that RPD are associated with visual dissatisfaction, and this may be associated with a central pigmentary epitheliopathy that is sometimes seen within RPD eyes.